2011
DOI: 10.1051/0004-6361/201117048
|View full text |Cite
|
Sign up to set email alerts
|

Observing a column-dependentζin dense interstellar sources: the case of the Horsehead nebula

Abstract: Context. Observations of small carbon-bearing molecules such as CCH, C 4 H, c-C 3 H 2 , and HCO in the Horsehead nebula have shown these species to have higher abundances towards the edge of the source than towards the center. Aims. Given the determination of a wide range of values for ζ (s −1 ), the total ionization rate of hydrogen atoms, and the proposal of a column-dependent ζ(N H ), where N H is the total column of hydrogen nuclei, we desire to determine if the effects of ζ(N H ) in a single object with s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 65 publications
6
86
1
Order By: Relevance
“…Turner et al 2000). The dissociative recombination of the ions CH + (Rimmer et al 2012), C 2 H + 2 , and C 2 H + 3 also yield ethynyl molecules in dense molecular clouds (Mul & McGowan 1980). The C 2 H molecules can themselves be photodissociated back to form C 2 and C 2 H + (Fuente et al 1993).…”
Section: H (Ethynyl)mentioning
confidence: 99%
“…Turner et al 2000). The dissociative recombination of the ions CH + (Rimmer et al 2012), C 2 H + 2 , and C 2 H + 3 also yield ethynyl molecules in dense molecular clouds (Mul & McGowan 1980). The C 2 H molecules can themselves be photodissociated back to form C 2 and C 2 H + (Fuente et al 1993).…”
Section: H (Ethynyl)mentioning
confidence: 99%
“…Montmerle 2010) raised the questions about the origin of the CR flux that generates such a high ionisation rate and how to reconcile these values with those ones measured in denser clouds that are more than one order of magnitude lower. A number of studies approached this problem using different strategies, analysing the effects of Alfvén waves on CR streaming (Skilling & Strong 1976;Hartquist et al 1978;Padoan & Scalo 2005;Rimmer et al 2012), magnetic mirroring and focusing (Cesarsky & Völk 1978;Chandran 2000;Padovani & Galli 2011), or the possible existence of a low-energy flux of CR particles able to ionise diffuse but not dense clouds (Takayanagi 1973;Umebayashi & Nakano 1981;McCall et al 2003;Padovani et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This last point has indeed been explored in Rimmer et al (2012), who studied the influence of the cosmic-ray ionization rate and showed that high value of ζ -either a fixed ζ ∼ 10…”
Section: Small Hydrocarbon Casementioning
confidence: 88%
“…On the other hand, in the PAH region the hydrocarbon abundances seem not to depend much on ζ, probably becauce in this region, the hydrocarbon chemistry is dominated by photon interactions than by cosmic-rays'. It should thus be worthwhile to further explore the impact of the cosmic-ray ionization rate in our model to see how it impacts the chemistry and if it helps to reproduce better the small hydrocarbons in the PAH region, even though Rimmer et al (2012) found with their model that it does not.…”
Section: Small Hydrocarbon Casementioning
confidence: 99%
See 1 more Smart Citation